A prospective 2-site parallel intervention trial of a research-based film to increase exercise amongst older hemodialysis patients. Issue 1 (December 2017) - Kontos, Pia; Alibhai, Shabbir; Miller, Karen-Lee; Brooks, Dina; Colobong, Romeo; Parsons, Trisha; Jassal, Sarbjit; Thomas, Alison; Binns, Malcolm; Naglie, Gary
Abstract Background Evidence suggests that exercise training for hemodialysis patients positively improves morbidity and mortality outcomes, yet exercise programs remain rare and are not systematically incorporated into care. We developed a research-based film, Fit for Dialysis, designed to introduce, motivate, and sustain exercise for wellness amongst older hemodialysis patients, and exercise counseling and support by nephrologists, nurses, and family caregivers. The objective of this clinical trial is to determine whether and in what waysFit for Dialysis improves outcomes and influences knowledge/attitudes regarding the importance of exercise for wellness in the context of end-stage renal disease. Methods/Design This 2-site parallel intervention trial will recruit 60 older hemodialysis patients from two urban hospitals. The trial will compare the film + a 16-week exercise program in one hospital, with a 16-week exercise-only program in another hospital. Physical fitness and activity measures will be performed at baseline, 8 and 16 weeks, and 12 weeks after the end of the program. These include the 2-min Walk Test, Grip Strength, Duke Activity Status Index, and the Timed Up-and-Go Test, as well as wearing a pedometer for one week. Throughout the 16-week exercise program, and at 12 weeks after, we will record patients' exercise using the Godin Leisure-time Exercise Questionnaire. Patients will also keep a diary of the exercise that they do at home on non-dialysis days. Qualitative interviews, conducted at baseline, 8, and 16 weeks, will explore the impact ofFit for Dialysis on the knowledge/attitudes of patients, family caregivers, and nephrology staff regarding exercise for wellness, and in what ways the film is effective in educating, motivating, or sustaining patient exercise during dialysis, at home, and in the community. Discussion This research will determine for whomFit for Dialysis is effective, why, and under what conditions. IfFit for Dialysis is proven beneficial to patients, nephrology staff and family caregivers, research-based film as a model to support exercise promotion and adherence could be used to support the National Kidney Foundation's guideline recommendation (NKF-KDOQI) that exercise be incorporated into the care and treatment of dialysis patients. Trial registration NCT02754271 (ClinicalTrials.gov), retroactively registered on April 21, 2016.